2018
DOI: 10.1002/jbmr.3418
|View full text |Cite
|
Sign up to set email alerts
|

Serum DHEA and Its Sulfate Are Associated With Incident Fall Risk in Older Men: The MrOS Sweden Study

Abstract: The adrenal-derived hormones dehydroepiandrosterone (DHEA) and its sulfate (DHEAS) are the most abundant circulating hormones and their levels decline substantially with age. Many of the actions of DHEAS are considered to be mediated through metabolism into androgens and estrogens in peripheral target tissues. The predictive value of serum DHEA and DHEAS for the likelihood of falling is unknown. The aim of this study was, therefore, to assess the associations between baseline DHEA and DHEAS levels and incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Since DHEA can increase IGF‐1 expression (Liang et al, 2016; Lin et al, 2019), the beneficial effect of DHEA + COC combination therapy is most likely due to this counterbalancing effect. Although lower DHEAS levels have been shown to predict increased bone resorption and low BMD in patients with AN and the elderly (Gordon et al, 2002; Miller et al, 2007; Ohlsson et al, 2017; Ohlsson et al, 2018), DHEA supplementation does not appear to have a direct beneficial effect on bone health as seen in the elderly and healthy adults. This observation has two major consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Since DHEA can increase IGF‐1 expression (Liang et al, 2016; Lin et al, 2019), the beneficial effect of DHEA + COC combination therapy is most likely due to this counterbalancing effect. Although lower DHEAS levels have been shown to predict increased bone resorption and low BMD in patients with AN and the elderly (Gordon et al, 2002; Miller et al, 2007; Ohlsson et al, 2017; Ohlsson et al, 2018), DHEA supplementation does not appear to have a direct beneficial effect on bone health as seen in the elderly and healthy adults. This observation has two major consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cortisol levels in the mornings occur at least in the first 6 months after bereavement, often accompanied with decreased levels of dehydroepiandrosterone (DHEA) [3]. Studies have shown an increased risk for falls and fractures in older men with low levels of DHEA [32,33]. When compared with married ones, widows were more likely to demonstrate worse coping behaviour in terms of more smoking and drinking.…”
Section: Bereavement and Physiological Effectsmentioning
confidence: 99%
“…Several reports have highlighted that patients with either Cushing's syndrome or ACS have lower levels of DHEA and androstenedione than subjects bearing nonfunctioning tu mors and controls, independently of age [26,27]. The relationship between sarcopenia, androgens, and risk of fall has been highlight ed in a very recent large populationbased studies, showing that lower DHEA and DHEAsulphate were associated with increased in cidence of falls [45].…”
Section: Risk Of Bone Fracturesmentioning
confidence: 99%